Borobudur as a Cosmological Communication System: The Main Stupa as a Giant Gnomon in Javanese Buddhist Tradition - Setiawan, Deni; Lasiyo; Ariani, Iva (INJECT (Interdisciplinary Journal of Communication), 2026)
This research looks at the main stupa at Borobudur and how it works like a big shadow tool for the sky. It seems tied to older Javanese views on the universe and what people knew about farming back then. Sources on old astronomy and building studies were compared in a descriptive way, along with some historical notes. The layout and carvings probably hold details on time and crops, so the monument could pass things along to people nearby. I think the shadows line up at certain points in the year with a local calendar that splits the seasons into twelve. That part feels like it helped share practical knowledge with farmers around the area. Some of the alignments might connect to Buddhist ideas too, but it is not totally clear how far that goes. The design has layers that do not always fit together neatly in what gets discussed. This paper brings together archeoastronomy and communication theory in a new framework. It fills a gap by treating cosmological communication as layers of symbols and environmental knowledge that get passed on. I think that part stands out as useful, but maybe it oversimplifies the connections. The findings point to a need for stronger heritage protection. Not just the buildings, but the living knowledge about the cosmos that stays tied to them. Using secondary sources has some limits, though. It feels like primary field observations and direct solar measurements could help later studies. Some details might still need checking in person.